1998
DOI: 10.1126/science.282.5397.2263
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of T Cell Inactivation by CTLA-4

Abstract: CTLA-4, a negative regulator of T cell function, was found to associate with the T cell receptor (TCR) complex ζ chain in primary T cells. The association of TCRζ with CTLA-4, reconstituted in 293 transfectants, was enhanced by p56 lck -induced tyrosine phosphorylation. Coexpression of the CTLA-4–associated tyrosine phosphatase, SHP-2, resulted in dephosphorylation of TCRζ bound to CTLA-4 and abolished the p56 lck -inducible TCRζ–CTLA-4 interaction. Thus, CTLA-4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
432
3
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 618 publications
(449 citation statements)
references
References 28 publications
11
432
3
3
Order By: Relevance
“…Activated or memory-type T cells including T cell clones may be susceptible to an alternative inhibitory mechanism through TR-CTLA-4 that does not require the cytoplasmic domain of CTLA-4. Since it is clear that the present study more closely reflects physiological function than the previous study, the obvious requirement of the cytoplasmic domain of CTLA-4 for its inhibitory function may suggest the importance of the assembly of the CTLA-4 tail with inhibitory molecules including SHP-2 [18,20] or regulatory molecules such as PP2A [22,23]. Further studies are needed to clarify the in vivo inhibitory mechanism through CTLA-4 in different stages of T cell development.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Activated or memory-type T cells including T cell clones may be susceptible to an alternative inhibitory mechanism through TR-CTLA-4 that does not require the cytoplasmic domain of CTLA-4. Since it is clear that the present study more closely reflects physiological function than the previous study, the obvious requirement of the cytoplasmic domain of CTLA-4 for its inhibitory function may suggest the importance of the assembly of the CTLA-4 tail with inhibitory molecules including SHP-2 [18,20] or regulatory molecules such as PP2A [22,23]. Further studies are needed to clarify the in vivo inhibitory mechanism through CTLA-4 in different stages of T cell development.…”
Section: Discussionmentioning
confidence: 63%
“…Although it has been suggested that several molecules, such as Src homology 2-containing protein tyrosine phosphatase-2 (SHP-2) and phosphatidyl inositol 3-kinase (PI3K), may mediate the negative signal through binding to the phosphorylated tyrosine motif (YVKM) present in the cytoplasmic region of CTLA-4 [18][19][20], the precise inhibitory mechanism remains controversial [21][22][23]. We and others have previously shown that the PI3K/ SHP-2 binding sites are not essential for CTLA-4-mediated inhibitory signals in T cell clones/cell lines [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that the significantly lower CD28 antigen expression on both subsets of unstimulated T cells and its more profound and long-lasting downregulation after stimulation compared with normal controls as observed in our study may deliver a stronger and prolonged stimulus for CD152 induction and expression on the CD3 þ / CD4 þ and CD3 þ /CD8 þ T-cell subpopulations in B-CLL. Since CD152 inhibits T-cell responses, increased expression of CD152 molecule on both subsets of T cells may result in an impairment of T-cell function in patients with B-CLL (Bartik et al, 1998;Lee et al, 1998;Metzler et al, 1999;Carreno et al, 2000;Frydecka et al, 2003;Wolowiec et al, 2003). This hypothesis was confirmed by our previously reported results, which showed strong negative correlations between the proportion of PB CD3 þ / CD152 þ cells and proliferative activity, IL-2 and IFN-g production in patients with Hodgkin's disease and healthy subjects .…”
Section: Discussionmentioning
confidence: 99%
“…It has been described earlier that SHP-2 is able to interact directly or indirectly with the inhibitory coreceptor CTLA-4 (CD152) [22][23][24][25]. For this reason, transduced T cells were re-stimulated with anti-CD3 and anti-CD28 or anti-CD3, anti-CD28 and anti-CTLA4 coupled to microspheres to induce either no or a strong CTLA-4 signal.…”
Section: Activation and Proliferation Are Intact In Individual T Lympmentioning
confidence: 99%
“…On the other hand, SHP-2 has been attributed to relay the inhibitory signals from over-expressed Gab2 [20], although other results show that instead PI3K is mediating this inhibitory effect [21]. Additionally, SHP-2 can be co-precipitated with the inhibitory coreceptor CTLA-4 (CD152) and CD3-f, which has led to the hypothesis that SHP-2 mediates inhibitory signals from CTLA-4 [22][23][24][25]. Furthermore, other inhibitory molecules, such as PD-1 and BTLA, containing the canonical ITIM as well as ITSM motifs were shown to recruit SHP-2 in a phosphorylation-dependent manner [26,27].…”
Section: Introductionmentioning
confidence: 99%